Faktor Eksternal dan Internal yang Mempengaruhi Stigma terhadap Orang dengan Epilepsi di Kalangan Akademisi - Manglapy, Yusthin Meriantti; Fani, Tiara (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2018)
Background: People with epilepsy needs to improve their quality of life. Stigma plays an important and significant role in decreasing the quality life of epilepsy patients. Factors that affect the stigma towards epilepsy patients in academic community has not been studied currently. This study aims to examine the internal and external factors which influence to the stigma towards epilepsy patients in private university in Semarang.Method: This study employs an observational technique using a cross-sectional approach by selecting 236 individuals from the academic community at aged 18 or older. Sociodemographic data and external and internal factors data were collected by face to face interviews. Whereas, the stigma was measured based on stigma scale.Results: Research findings revealed that 54.5% of the respondents give stigma with the score >20.73. The multiple logistic regression test revealed that factors influence the stigma were as follows, people/respondents had an experience of seeing epileptic seizures are more likely to have in giving stigma as much as 1,8 times compare with inexperience of seeing epileptic seizures (OR= 1.86), and having relatives/peers with epilepsy as protective variable of giving stigma (OR= 0.45). Education and socialization are necessary to be provided to the community in order to improve knowledge and positive attitudes and reduce stigma.Keywords: Stigma, epilepsy, quality of life, people with epilepsy